Review of the Current Basic Science Strategies to Treat Critical Limb Ischemia. (May 2019) - Haghighat, Leila; Ionescu, Costin N.; Regan, Christopher J.; Altin, Sophia Elissa; Attaran, Robert R.; Mena-Hurtado, Carlos I.
Critical limb ischemia (CLI) is a highly morbid disease with many patients considered poor surgical candidates. The lack of treatment options for CLI has driven interest in developing molecular therapies within recent years. Through these translational medicine studies in CLI, much has been learned about the pathophysiology of the disease. Here, we present an overview of the macrovascular and microvascular changes that lead to the development of CLI, including impairment of angiogenesis, vasculogenesis, and arteriogenesis. We summarize the randomized clinical controlled trials that have used molecular therapies in CLI, and discuss the novel imaging modalities being developed to assess the efficacy of these therapies.